2022
DOI: 10.3390/polym14030594
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization and Anticancer Enhancing Activity of the Peptide Nisin by Cyclodextrin-Based Nanosponges against Colon and Breast Cancer Cells

Abstract: The great variability of cancer types demands novel drugs with broad spectrum, this is the case of Nisin, a polycyclic antibacterial peptide that recently has been considered for prevention of cancer cells growth. As an accepted food additive, this drug would be very useful for intestinal cancers, but the peptide nature would make easier its degradation by digestion procedures. For that reason, the aim of present study to investigate the protective effect of two different β-cyclodextrin-based nanosponges (carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 65 publications
5
27
0
Order By: Relevance
“…In this study, we used the same conditions to prepare the complexes. However, the results of our previous study relatively confirmed the complex formation between nisin Z and both nanosponges by SEM techniques while providing the clearest evidence regarding DLS results and the effect of both NSs to change the release profile of nisin Z [ 33 ], as is supported by different publications [ 43 , 44 ]. In this study, a DSC method was carried out to determine the complex formation, with unsuccessful results; for this reason, we carried out FTIR as another validation test, but the results were unclear ( Figure 1 A).…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…In this study, we used the same conditions to prepare the complexes. However, the results of our previous study relatively confirmed the complex formation between nisin Z and both nanosponges by SEM techniques while providing the clearest evidence regarding DLS results and the effect of both NSs to change the release profile of nisin Z [ 33 ], as is supported by different publications [ 43 , 44 ]. In this study, a DSC method was carried out to determine the complex formation, with unsuccessful results; for this reason, we carried out FTIR as another validation test, but the results were unclear ( Figure 1 A).…”
Section: Resultssupporting
confidence: 80%
“…Our previous report [ 33 ] demonstrated the possibility of complexing nisin with nanosponges as an effective way to stabilize the peptide. Indeed, good encapsulation efficiency of 90% was found under optimized conditions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations